Temperature insensitive current reference circuit using standard CMOS devices - Shima, T. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
In this paper, temperature insensitive current reference circuit is proposed. The reference current value is determined by using the threshold voltage controlled circuit. The main difference from the previous work (Georglou and Toumazou, 2002) is that the circuit can be fabricated by the standard CMOS process. The resistor and the transistor physical parameter temperature dependences are compensated with each other to determine the output reference current. The detail temperature performance is analyzed, and is evaluated by simulations.